2020
DOI: 10.1117/1.nph.7.3.035011
|View full text |Cite
|
Sign up to set email alerts
|

Short-channel regression in functional near-infrared spectroscopy is more effective when considering heterogeneous scalp hemodynamics

Abstract: . Significance: The reliability of functional near-infrared spectroscopy (fNIRS) measurements is reduced by systemic physiology. Short-channel regression algorithms aim at removing systemic “noise” by subtracting the signal measured at a short source–detector separation (mainly scalp hemodynamics) from the one of a long separation (brain and scalp hemodynamics). In literature, incongruent approaches on the selection of the optimal regressor signal are reported based on different assumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
115
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(122 citation statements)
references
References 79 publications
7
115
0
Order By: Relevance
“…Others have argued that it is necessary to record short-channel information as well as additional sources of physiology from multiple regions of the scalp to determine local influences of scalp hemodynamics and additionally remove them. 24 , 49 , 50 Another recent method for removing systemic information has been proposed that utilizes multi-distance tomographic recordings to separate superficial from cortical hemodynamics. 41 The effectiveness of short-channel regression has been further investigated and compared to recently developed methods that are also intended to separate systemic from cortical responses in fNIRS recordings.…”
Section: Introductionmentioning
confidence: 99%
“…Others have argued that it is necessary to record short-channel information as well as additional sources of physiology from multiple regions of the scalp to determine local influences of scalp hemodynamics and additionally remove them. 24 , 49 , 50 Another recent method for removing systemic information has been proposed that utilizes multi-distance tomographic recordings to separate superficial from cortical hemodynamics. 41 The effectiveness of short-channel regression has been further investigated and compared to recently developed methods that are also intended to separate systemic from cortical responses in fNIRS recordings.…”
Section: Introductionmentioning
confidence: 99%
“…While the systemic physiological interference distribute across all the channels over the head, our result showed relatively local spatial distribution of HbO and HbR concentration values mapped over the motor/premotor and frontal dorsolateral cortices ( Fig 2B ) using high-resolution optode distributed over most of the head ( Fig 1B ), however, we cannot completely exclude the influence of these confounding factors. Hence, one limitation of current study is that influence of DBS-induced decreases in skin blood flow cannot definitely be denied since changes in systemic physiological factors (e.g., cardiac, respiratory, and blood pressure fluctuations) can affect regional blood flow and some studies have revealed that skin blood flow changes, which can impact changes in HbO, are not homogeneous [ 147 149 ]. Therefore, the use of additional short-distance channels (<1 cm) is expected to provide a superior removal of the superficial systemic factors on functional near-infrared spectroscopy [ 149 , 150 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, one limitation of current study is that influence of DBS-induced decreases in skin blood flow cannot definitely be denied since changes in systemic physiological factors (e.g., cardiac, respiratory, and blood pressure fluctuations) can affect regional blood flow and some studies have revealed that skin blood flow changes, which can impact changes in HbO, are not homogeneous [ 147 149 ]. Therefore, the use of additional short-distance channels (<1 cm) is expected to provide a superior removal of the superficial systemic factors on functional near-infrared spectroscopy [ 149 , 150 ].…”
Section: Discussionmentioning
confidence: 99%
“…Later, most resting-state fMRI studies have adopted GSR as a pre-processing approach: the global signal component is regressed out of preprocessed BOLD signals prior to computation of connectivity measures and therefore regionally focused connectivity patterns are reported (Fox et al, 2009). Similarly, in recent fNIRS studies of resting state brain, a global component has been recognized in the measurements from regularly distanced optodes (White et al, 2009;Mesquita et al, 2010;Tong and Frederick, 2010;Eggebrecht et al, 2014;Tachtsidis and Scholkmann, 2016;Duan et al, 2018;Wyser et al, 2020) and from short-distanced optodes (White et al, 2009;Gregg et al, 2010;Mesquita et al, 2010;Eggebrecht et al, 2014;Tachtsidis and Scholkmann, 2016;Duan et al, 2018;Sherafati et al, 2020;Wyser et al, 2020). To date, there is no wellestablished pre-processing routine in resting state fNIRS studies although multiple efforts are being made (Huppert et al, 2009;Ye et al, 2009;Xu et al, 2014;Santosa et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The most common RSFC analysis of fNIRS data involves evaluating the temporal relationship between time series of the preprocessed data from recording units, for example, through the Pearson’s correlation. A global component has been observed in fNIRS measurements and commonly removed for the purpose of attenuating systematic noises at the resting state ( White et al, 2009 ; Gregg et al, 2010 ; Mesquita et al, 2010 ; Eggebrecht et al, 2014 ; Tachtsidis and Scholkmann, 2016 ; Duan et al, 2018 ; Sherafati et al, 2020 ; Wyser et al, 2020 ). Whereas removing superficial contributions from short-distanced channels to fNIRS is increasingly employed to attenuate the systematic noises ( Saager and Berger, 2005 ; Gagnon et al, 2011 ), data from both long-distanced and short-distanced channels commonly suggest a global component exist in fNIRS measurements and distribute across wide regions ( Zhang et al, 2005 , 2007 , 2009 ; Kohno et al, 2007 ; Gregg et al, 2010 ; Tong and Frederick, 2010 ; Novi et al, 2016 ; Sato et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%